Medición del riesgo de renta variable mediante modelos internos en Solvencia II - Pablo Durán Sontomil; Luis A. Otero González; José A. Redondo López; M. Milagros Vivel Búa (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
This work focuses on developing an internal model for equity risk under Solvency II. We have used monthly data for the series of Ibex 35, Cac 40, FTSE 100 and Dax in the period between January 1992 and December 2008. This work fits by maximum likelihood method the model of normal returns, based on the standard model of QIS4, compared to the mixture of normal and a Markov regime switching model. The analyzed models are compared based on criteria of parsimony and normality of the residuals. Subsequently, we compared capital requirements resulting from applying these models against the standard formula of QIS4. The results showed that the funds needed to take the equity risk are dependent on the specification used.
Keywords: G22; G28; 330; internal models; equity risk; Solvency II